Sensitivity of the saving rate to the interest rate in the United States of America - Tomko, Adam; Potužák, Pavel; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The relationship between the saving rate and interest rate remains a topic of interest. This thesis examines the relationship between these two variables in the United States of America, utilizing quarterly data from the second quarter of 2003 to the fourth quarter of 2023. While empirical evidence does not confirm the sensitivity of the net private savings rate to the real interest rate, it does indicate a responsiveness to the nominal interest rate. The primary analysis is structured into two main sections. The first section investigates the relationship between the net private savings rate and the real interest rate, while the second section examines the relationship between the net private savings rate and the nominal interest rate. This thesis builds upon previous research by including undistributed corporate profits as a saving component, given the potential for substitutability. Moreover, it incorporates a model of inflation expectations and employs advanced econometric techniques to elucidate the dynamic relationship among the variables.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses